Perlindungan Hukum Konsumen Dalam Perjanjian Pinjaman Online - Nisa Riska Wahyu; Liza Puspita; Nia Alfitrianti; Fitri Ramadhani; Nur Azizah Aryeti (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The rapid growth of providers of information technology-based money lending and borrowing services has apparently not been balanced with adequate education for the public, giving rise to various effects/risks arising from the large number of types of online loans and the fact that many companies are still found providing unregistered or illegal providers as well as the potential for personal data to be leaked. users that can be misused by the organizing company or other parties. Consumer protection is intended as all efforts to guarantee legal certainty to provide consumer protection, as in Article 1 number 1 UUPK. The existence of this UUPK is to guarantee legal certainty for consumer protection and the fulfillment of consumer rights